Ethical Principles in AI Use for Assessment: Exploring Students' Perspectives on Ethical Principles in Academic Publishing - Alexandra Maria Lazăr (Cățeanu); Angela Repanovici; Daniela Popa; Diana Geanina Ionas; Ada Ioana Dobrescu (MDPI AG, 2024)
Students' comprehension of ethical principles and their application in the realm of AI technology play a crucial role in shaping the efficacy and morality of assessment procedures. This study seeks to explore students' viewpoints on ethical principles within the context of AI-driven assessment activities to illuminate their awareness, attitudes, and practices concerning ethical considerations in educational environments. A systematic review of articles on this topic was conducted using scientometric methods within the Web of Science database. This review identified a research gap in the specialized literature regarding studies that delve into students' opinions. Subsequently, a questionnaire was administered to students at Transilvania University of Brasov as part of the Information Literacy course. Statistical analysis was performed on the obtained results. Ultimately, students expressed a desire for the Information Culture course to incorporate a module focusing on the ethical use of AI in academic publishing.